Particulate composite iridium oxide material and method of manufacturing the same and uses
Patent Information
- Application Number
- KR1020267022383
- Authority / Receiving Office
- KR · KR
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2023-12-19
- Filing Date
- 2024-12-19
- Publication Date
- 2026-08-14
Smart Images

Figure PCT00003_ABST
Abstract
Description
Technology Field
[0001] The present invention relates to an iridium oxide film particle catalyst, a method for manufacturing a particulate composite material comprising a uniformly distributed iridium metal or iridium oxide layer, and a use of the particulate composite material in a catalyst composition that can be used for water electrolysis. Background Technology
[0002] Various useful particulate catalysts for electrolysis, including precious metals, particularly platinum group metals, have been disclosed in the prior art. These catalysts generally comprise an inorganic support, upon which a catalytic metal or metal oxide is deposited through precipitation and / or crystallization from a solution.
[0003] For example, EP4019666A1 describes a coating having an average layer thickness in the range of 1.5 to 5.0 nm and comprising iridium oxide, iridium hydroxide, or iridium oxide hydroxide, with an iridium content of up to 50 wt%, wherein the BET specific surface area is 2 to 50 m² 2 Disclosed is a particle catalyst precipitated on a support material having a g / g and composed of an oxide of a transition metal, an oxide of a main group metal, and / or SiO2.
[0004] Likewise, EP2608297 discloses a particle catalyst comprising silica or titania particles having a high specific surface area, upon which iridium oxide is deposited through precipitation from a precursor solution.
[0005] US20140322631A1 comprises an iridium oxide coating, 25 to 70 weight percent of an inorganic oxide carrier based on the total catalyst weight, and 30 to 200 m 2 A catalyst having a BET specific surface area of / g is disclosed. This catalyst is described as having an electrical conductivity exceeding 0.01 S / cm based on powder measurements.
[0006] US7976989B2 has a BET specific surface area of 50 to 400 m² 2A composite catalyst is disclosed comprising iridium oxide particles deposited on or dispersed around inorganic oxide particles, with a weight of / g and less than 20% by weight based on the total weight of the composite catalyst. The catalyst further comprises ruthenium oxide such that the Ir / Ru atomic ratio is 1 / 4 to 1 / 4.
[0007] A disadvantage of these catalysts and similar catalysts is that the deposition of catalytic metal oxides during the precipitation step in the liquid solution is generally non-uniform. Furthermore, reaction kinetics and mass transfer change over time as the pH and other factors of the solution vary. Moreover, nucleation and crystal growth generally affect the size of the aggregates formed, which may result in some of the catalytic metal becoming inaccessible to the catalytic reaction.
[0008] US9450251B2 discloses a method for manufacturing an anode material for a fuel cell, comprising synthesizing an electrolytic catalyst by depositing a solid solution of iridium oxide and a valve metal oxide on a porous titania substrate by atomic layer deposition (ALD). Likewise, US20190109330A1 discloses a catalyst material manufactured by ALD, wherein the catalyst material comprises a support comprising a material selected from the group consisting of metal carbides, nitrides, oxides, and combinations thereof, and a thin film covalently bonded to the support and having a thickness of 0.5 to 5.0 nm, wherein the thin film comprises a catalyst metal selected from the group consisting of platinum group metals, platinum group metal oxides, transition metals, transition metal oxides, and combinations thereof. In both cases, the ALD process was performed by applying a vacuum purging step.
[0009] However, the applicant found that the disclosed catalyst based on a metal oxide substrate may have limited electrical conductivity, which makes it difficult to use as an electrocatalyst because it requires a high voltage that can lead to unwanted side reactions. Additionally, through research on fuel cell membranes, it is known that certain metal oxide supports, particularly titania, can react with hydrogen peroxide to generate hydroxyl radicals, which can have a negative effect on the stability of the hydrogen-permeable ionomer layer in proton exchange membrane electrolytic cells or fuel cells.
[0010] EP1701790B1 discloses a precious metal-based oxide catalyst for water electrolysis, wherein the catalyst comprises iridium oxide and a high specific surface area inorganic oxide, and the inorganic oxide is present in an amount of less than 20 weight percent based on the total weight of the catalyst. If the amount of the inorganic oxide exceeds 20 weight percent, the electrical conductivity of the catalyst and the electrode decreases. Consequently, such a catalyst contains a large amount of precious metal oxide, resulting in high costs, and it is not possible to achieve a very low loading of precious metal on the electrode. Therefore, even when using the catalyst disclosed in EP1701790B1, the consumption of precious metal remains relatively high, leading to an increase in the environmental cost of the catalyst product.
[0011] WO2022015161A1 discloses a process for coating iridium oxide onto particulate titanium oxide, wherein the particulate substrate is generated in situ within a film or electrode, i.e., a porous substrate, before being coated by Atomic Layer Deposition (ALD) technology, thereby forming core-shell nanoparticles within the porous substrate. The formation of a core-shell structure within the porous substrate implies that the porous substrate influences the formation of the core-shell structure. Depending on the substrate and reaction conditions used, a non-uniform shell may be formed, or the coating may be applied to the porous substrate itself instead of just to the particles. The core-shell nanoparticles may have various shapes, such as a dumbbell shape in which the core is partially surrounded by a shell. To obtain a sufficient number of core-shell nanoparticles, a number of cycles, though not explicitly defined, may be required, and the catalyst precursor must be carefully selected to avoid reacting with the support material. US20210252486A1 discloses a technology for applying Fe or FeOx on various substrates. The problem to be solved
[0012] The object of the invention of the present application is to provide a material suitable as a catalyst for electrochemical reactions such as water electrolysis and a use of said catalyst particles. Another object is to provide an improved method for manufacturing the particle catalyst according to the present invention. means of solving the problem
[0013] In light of the above discussion, the present disclosure provides a method for forming an iridium oxide film by chemical vapor deposition at a pressure of 80 to 1010 kPa on a particulate substrate having an electrical conductivity exceeding 0.01 S / cm on a powder measurement basis, and the method comprises the following steps:
[0014] (i) a step of providing a particulate substrate in a reaction chamber;
[0015] (ii) a step of contacting the above-mentioned particulate substrate with a vaporized iridium oxide precursor gas to form a film of iridium precursor material uniformly distributed on the substrate;
[0016] (iii) a step of contacting a material including the uniformly distributed film with a vaporized oxidizing agent so that the oxidizing agent reacts with the uniformly distributed iridium precursor film on the substrate; and
[0017] (iv) optionally repeating steps (ii) and (iii) until a surface film of the desired thickness is obtained;
[0018] Accordingly, a particle material having a surface film of a desired thickness is obtained, comprising uniformly distributed individual iridium oxide clusters with an average diameter in the range of 0.3 to 5 nm.
[0019] Another objective is to provide a particle material obtainable by the method according to the present disclosure. Another objective is to provide a method for forming an electrolytic electrode comprising using an electrocatalyst according to the present disclosure. In another aspect, an object of the present invention is to provide an electrocatalyst assembly comprising catalyst particles according to the present disclosure.
[0020] Another objective is to provide a battery comprising a catalyst material according to the present invention or a composition according to the present invention.
[0021] Another objective is to provide an application for the material according to the present invention in a water electrolysis device, a fuel cell, or a bidirectional fuel cell.
[0022] The applicant has confirmed that the above objective is achieved by the method, material, composition, and electrolytic cell according to the present invention. Brief explanation of the drawing
[0023] The present invention is described below with reference to embodiments illustrated in the accompanying drawings, and FIG. 1 shows the shape of an iridium oxide (IrOx) catalyst according to a preferred embodiment of the present disclosure using a transmission electron microscope (TEM) image. FIG. 2 shows the mass activity, electrochemical active area (ECA), and durability of two catalyst compositions according to a preferred embodiment of the present disclosure in a rotating disc electrode (RDE) electrochemical test compared with Iridium Black, a commercial iridium oxide catalyst, comparing durability relative to activity. FIG. 3 shows the iridium oxidation state of various catalyst compositions according to a preferred embodiment of the present disclosure, using X-ray photoelectron spectroscopy (XPS), ranging from amorphous Ir (iii) to more oxidized Ir (iv). FIG. 4 illustrates a current density of 0.5 times that a catalyst composition according to a preferred embodiment of the present disclosure exhibits while using 15 to 30 times less iridium than a commercially available comparative catalyst in a membrane electrode assembly (MEA) test. Figure 5 shows the change in electrical conductivity when etching treatment is performed on a particulate starting material and a calcined catalyst composition. Figure 6 is a graph showing the relationship between cell voltage and current density at the initial performance (BoL) of the catalyst particles measured in the MEA test. Comparative example of catalysts with different iridium loading amounts and Iridium Black It is a city. Figure 7 is a graph showing the relationship between voltage and current density at the initial performance (BoL) in the MEA test, the start time (BoT) of the accelerated degradation test, and the end time (EoT) of the accelerated degradation test. Specific details for implementing the invention
[0024] The present invention is described in more detail with reference to the accompanying drawings, which illustrate embodiments of the invention. However, the present invention may be embodied in various forms and should not be interpreted as being limited to the embodiments described herein. Rather, such embodiments are provided to make the disclosure thorough and complete and to fully convey the scope of the invention to those skilled in the art. In the drawings, the sizes and relative sizes of layers and regions may be exaggerated for clarity.
[0025] Where one element or layer is described as being "on," "connected to," or "coupled to" another element or layer, this means that it may be located directly on, directly connected to, or coupled to the other element or layer, or that one or more other elements or layers may be interposed between them. Conversely, where one element is described as being "directly on," "directly connected to," or "directly coupled to" another element or layer, no other elements or layers are interposed between them. Identical reference numerals denote identical elements throughout the specification. Additionally, the term "and / or" in this specification includes all possible combinations of one or more items listed together.
[0026] In this specification, terms such as "first," "second," etc., may be used to describe various elements, components, regions, layers, and / or parts; however, such elements, components, regions, layers, and / or parts are not limited by these terms. These terms are used merely to distinguish one element, component, region, layer, or part from another element, component, region, layer, or part. Accordingly, the first element, component, region, layer, or part described below may be referred to as the second element, component, region, layer, or part without departing from the spirit of the invention.
[0027] Spatial relative terms such as "beneath," "below," "lower," "above," and "upper" may be used to describe the relationship between one element or feature and another element or feature as illustrated in the drawings. These spatial relative terms should be understood to include not only the directions illustrated in the drawings but also different directions of the device during use or operation. For example, if the device in the drawings is inverted, an element described as being "below" or "below" another element or feature will be located "above" the other element or feature. Accordingly, the exemplary term "beneath" may include both directions of up and down. Additionally, the device may be positioned in different directions (e.g., rotated 90 degrees or in a different direction), and the spatial relative terms used herein should be interpreted accordingly.
[0028] The terms used herein are for describing specific embodiments only and are not intended to limit the invention. The singular forms “a,” “an,” and “the” used herein are intended to include the plural forms unless the context clearly indicates otherwise. Additionally, the terms “comprises” and / or “comprising” in this specification mean the presence of the described features, integers, steps, actions, elements, and / or components, but do not exclude the presence or addition of one or more other features, integers, steps, actions, elements, components, and / or groups thereof.
[0029] Unless otherwise defined, all terms used herein (including technical and scientific terms) have the same meaning as generally understood by a person skilled in the art to which the present invention pertains. Furthermore, terms defined in commonly used dictionaries should be interpreted in a meaning consistent with their meaning in the relevant technical field and should not be interpreted in an ideal or overly formal sense unless explicitly defined in this specification.
[0030] Embodiments of the present invention are described with reference to cross-sectional views schematically illustrating ideal embodiments of the present invention. Accordingly, it is expected that differences from the shapes in the drawings may occur, for example, due to manufacturing techniques and / or tolerances. Therefore, embodiments of the present invention should not be interpreted as being limited to the shapes of specific regions depicted in this specification, and should be understood to include variations in shape that occur, for example, during the manufacturing process. For example, an etching region depicted as a rectangle generally has rounded or curved corners. Accordingly, the regions depicted in the drawings are schematic, and their shapes are not intended to represent the exact shape of the device region, nor are they intended to limit the scope of the present invention.
[0031] The inventors have surprisingly discovered that by selecting a particulate substrate having an electrical conductivity exceeding 0.01 S / cm based on powder electrical conductivity measurement standards and performing chemical vapor deposition at a pressure in the range of 80 to 1010 kPa, an electrocatalytic material with a particularly excellent ratio of mass activity to durability can be produced. Accordingly, the present invention generally relates to a method for manufacturing a thin film by chemical vapor deposition, more specifically to an atomic layer deposition (ALD) process performed at atmospheric pressure or a pressure close to atmospheric pressure, and even more specifically to an atomic layer deposition (ALD) process of continuous supply of precursor and oxidant that essentially does not require a purge step.
[0032] Atomic Layer Deposition (ALD) is a specific technique generally based on Chemical Vapor Deposition (CVD). CVD is a commonly used deposition process used to deposit layers onto a substrate from precursor vapor materials, typically at low pressure. By appropriately controlling the vacuum level, substrate temperature, and the temperature, concentration, and type of precursor material introduced into the reaction chamber, desired materials can be deposited with uniform thickness and high homogeneity. ALD is a variation of CVD in which deposition is achieved through sequential cycles based on atomic layer epitaxy (ALE), chemisorption, and reaction techniques. A typical ALD process disclosed in the literature is performed in a reaction chamber under severe reduced pressure, i.e., a vacuum chamber. Inside or before the chamber, the substrate is heated to an appropriate deposition temperature under reduced pressure. Subsequently, a reaction gas is introduced into the vacuum chamber and comes into contact with the substrate, thereby depositing or adsorbing a small amount of the reaction gas onto the substrate surface. This reaction gas can be introduced into the reaction chamber in the form of gaseous reaction gas pulses, which come into contact with the substrate surface to form a monolayer of the reactant on the substrate surface. Excess gas containing reactants is purged from the reaction chamber in the form of steam or gas and removed.
[0033] Subsequently, a second gaseous reactant is introduced into the reaction chamber and brought into contact with the surface of the coated substrate, allowing a surface reaction to occur between the first reactant and the second reactant bonded to the surface. Then, an additional purging step is performed to remove any excess of the second gaseous reactant and all vapor or gaseous byproducts generated by the reaction between the reactant layer and the uncoated substrate, thereby removing them from the reaction chamber. This step can be repeated until the reacted deposited film reaches a desired thickness.
[0034] Since the gas phase is purged before introducing the next gas, the phenomenon of the reactant and the oxidant reacting directly in the gas phase can be minimized. The removal or purging step may include purging using an inert gas (e.g., nitrogen, helium, or argon) under additional reduced pressure and / or reaction conditions. In this cycle, the surface of the substrate to be coated is first exposed to a first precursor gas, followed by purging to remove unreacted first precursor gas, and then contacted with a second precursor. The second precursor reacts in situ with the remaining or adsorbed first precursor to form a product film on the substrate surface. This cycle can be repeated until a film of the desired thickness is formed. However, processes using high vacuum require the creation and maintenance of a vacuum, so energy efficiency is relatively low.
[0035] This process has the advantage of being performed at atmospheric pressure or near-atmospheric pressure, thereby reducing the need to generate and maintain the very low pressures typically used in conventional ALD processes. Furthermore, since this process does not require a purging step to remove byproducts or unreacted reactants before introducing the next reactant pulse, it can effectively be considered a CVD process for particulate substrates. Because there is no need to remove unreacted reactants and byproducts, this process can be performed in a single reaction chamber with continuous feeding of powder and reactants, enabling fully continuous operation. Particularly suitable reactors include, for example, the continuous pneumatic transfer reactor disclosed in US20210102288A1.
[0036] The process comprises at least the following steps: providing a particulate substrate in a reaction chamber; contacting the particulate substrate with a vaporized iridium oxide precursor gas to form a film of iridium precursor material uniformly distributed on the substrate; contacting the material including the uniformly distributed layer with a vaporized oxidizing agent to cause the oxidizing agent to react with the iridium precursor film uniformly distributed on the substrate; and optionally repeating these steps sequentially, thereby obtaining a particulate material having a surface film of a desired thickness comprising uniformly distributed individual iridium oxide clusters having an average diameter in the range of 0.3 to 5 nm.
[0037] Accordingly, the method according to the present disclosure preferably further comprises the step of sequentially exposing a particulate substrate to a gaseous iridium precursor and a gaseous oxidizing agent, and depositing an iridium material on the substrate.
[0038] Additionally, a step of removing excess iridium oxide precursor gas, excess reaction gas, and / or reaction by-products from the reaction chamber may be optionally applied. However, in order to improve the production rate, in the method according to the present disclosure, it is preferable not to remove excess iridium oxide precursor gas, excess reaction gas, and / or reaction by-products from the reaction chamber.
[0039] Preferably, in the method according to the present disclosure, steps (ii) and (iii) are in which an iridium oxide precursor gas is supplied to cause a self-terminating reaction with the surface of a particulate substrate, and an oxidizing agent is supplied to cause a self-terminating reaction with a precursor material comprising a continuous layer of iridium oxide.
[0040] Preferably, in the method according to the present disclosure, steps (i) to (iv) are performed at atmospheric pressure or a pressure close to atmospheric pressure.
[0041] Particulate Substrate
[0042] Preferably, in the method according to the present disclosure, an iridium oxide film having an electrical conductivity exceeding 0.01 S / cm on a powder measurement basis is formed by chemical vapor deposition at a pressure in the range of 80 to 1010 kPa.
[0043] In the above method, it is preferable that the substrate or iridium support material is essentially inert under oxidizing and acidic conditions, and more preferably, the support material is inert during the deposition of the iridium oxide layer, calcination, and use in a PEM electrolytic cell.
[0044] The above substrate can be coated with iridium oxide under process conditions and is a particulate material that is essentially inert with respect to process conditions.
[0045] When applying this method, on a particulate substrate material having an average particle size defined below, the electrical conductivity of the generated catalyst material is within a range suitable for manufacturing an electrode with sufficiently high performance.
[0046] Generally, the electrical conductivity of the resulting composite precious metal oxide catalyst exceeds 0.01 S / cm at a pressure of 300 kPa, and preferably exceeds 0.1 S / cm at a pressure of 300 kPa (3 bar). As a result, the electrochemical mass activity (measured as current density [A / mg Ir] at 1.5 V versus RHE) is generally in the range of 100 to 15,000 mA / mg Ir.
[0047] Preferably, in the method according to the present disclosure, the particulate support material comprises metal oxides, carbides, borides, nitrides, and non-metal oxides and / or carbides.
[0048] Preferably, in one embodiment, the particulate substrate is selected from inorganic metal oxides, and more preferably from the group consisting of titania (TiO2), silica (SiO2), alumina (Al2O3), zirconia (ZrO2), tin dioxide (SnO2), fluorine-doped tin dioxide (SnO2 / F), ceria (CeO2), ceria-doped zirconia (CeO2 / ZrO2), niobium pentoxide (Nb2O5), tantalum pentoxide (Ta2O5), and mixtures and combinations thereof, or is selected from boron carbide materials or boron carbide composites with other compounds such as silicoboron carbide. Preferably, in the method according to the present disclosure, the inorganic oxide or boron carbide is added in a range of 30% to 60% by weight based on the total weight of the catalyst.
[0049] Preferably, the particle size of the support material is in the range of a weight-average particle size of 10 nm to 100 nm, and more preferably in the range of 40 nm to 60 nm.
[0050] In one or more embodiments, the iridium oxide-coated particle material contains boron at a concentration of 1 at%, 5 at%, 10 at%, 12 at%, 15 at%, 20 at%, 22 at%, 25 at% to 28 at%, 30 at%, 35 at%, 40 at%, 45 at%, 50 at%, 60 at%, or 70 at%. For example, particulate boron carbide coated with iridium oxide is 1 at% to 70 at%, 1 at% to 60 at%, 1 at% to 50 at%, 1 at% to 45 at%, 1 at% to 40 at%, 1 at% to 35 at%, 1 at% to 30 at%, 1 at% to 25 at%, 1 at% to 20 at%, 1 at% to 15 at%, 1 at% to 10 at%, 10 at% to 70 at%, 10 at% to 60 at%, 10 at% to 50 at%, 10 at% to 45 at%, 10 at% to 40 at%, 10 at% to 35 at%, 10 at% to 30 at%, 10 at% to 25 at%, 10 at% to 20 at%, It contains boron carbide at a concentration of 10 at% to 15 at%, 10 at% to 12 at%, 15 at% to 70 at%, 15 at% to 60 at%, 15 at% to 50 at%, 15 at% to 45 at%, 15 at% to 40 at%, 15 at% to 35 at%, 15 at% to 30 at%, 15 at% to 25 at%, or 15 at% to 20 at%.
[0051] The substrate must be a powdered material, inert, and have very low solubility in water and acidic environments. This is important for ensuring the long lifespan and high durability of the PEM electrolytic cell.
[0052] Preferably, the substrate is a material that withstands manufacturing conditions in a pneumatic reactor or a fluidized bed reactor without significant particle wear.
[0053] In some embodiments of the present invention, an iridium oxide layer is formed on a dielectric material. Examples of dielectric materials for a substrate include hafnium oxide (HfO2), aluminum oxide (Al2O3), titanium oxide (TiO2), yttrium oxide (Y2O3), zirconium oxide (ZrO2), tantalum oxide (Ta2O5), niobium oxide (Nb2O5), barium titanate (BaTiO3), and strontium titanate (SrTiO3). Particularly suitable substrates may include inorganic oxides with a high specific surface area, such as TiO2, Al2O3, ZrO2, and mixtures thereof. Particularly suitable inorganic oxide substrate materials include pyrogenic oxides such as TiO2, SiO2, or Al2O3. However, other inorganic oxides such as Nb2O5, SnO2, fluorine-doped tin oxide (SnO2 / F), zirconia (ZrO2), ceria-doped zirconia (CeO2 / ZrO2) and / or mixtures and combinations thereof may also be used.
[0054] Another particularly suitable type of substrate is selected from nitrides, e.g., titanium nitride (TiN), or carbide materials, e.g., titanium carbide (TiC) or tantalum carbide. Preferably, these materials include silicon or boron materials such as boron nitride or boron carbide and / or mixtures, alloys, and combinations thereof.
[0055] Boron carbide is used in various industrial fields, including abrasives, refractories, and neutron absorbers for nuclear power plants. Preferably, when used as a catalyst support for electrolysis, boron carbide substrates can be used because they offer an excellent balance between durability and intrinsic electrical conductivity.
[0056] When manufactured as a PEM stack or CCM, the boron carbide-based catalyst material was able to achieve a degradation level of about 1 μV / hour, which corresponds to the catalyst particles degrading by about 0.1% over 1000 hours.
[0057] Suitable boron carbide materials include essentially pure boron carbide materials or boron carbide complexes with other compounds such as silicon carbide. The chemical formula of boron carbide is generally B 12 Although it is C3, it is often simply referred to as B4C, the smallest unit. These boron carbide materials may contain oxygen, which can be formed during the CVD process or while stored in an ambient air environment.
[0058] In addition, it was confirmed that the catalyst particles according to the present invention manufactured from the above substrate generally exhibit an electrical conductivity exceeding at least 0.1 S / cm at a pressure of 300 kPa (3 bar).
[0059] These materials are generally considered covalent ceramic materials and belong to the category of materials with the highest hardness among commonly known materials. Therefore, these materials are particularly suitable for use in continuous circulation reactors or pneumatic transfer reactors because they exhibit minimal loss of catalyst material due to wear.
[0060] Iridium Oxide Precursor
[0061] Advantageously, the iridium oxide precursor comprises an organometallic complex of iridium. Preferably, the iridium oxide precursor comprises an iridium (C1 to C4-alkylcyclopentadienyl) complex, and more preferably, a methylcyclopentadienyl or ethylcyclopentadienyl complex. Preferably, in the method according to the present disclosure, the iridium oxide precursor is a heterolaptic metallocene complex.
[0062] Preferably, in the method according to the present disclosure, the (C1 to C4-alkylcyclopentadienyl) complex further comprises a diene ligand selected from linear or cyclic alkylenes, preferably selected from 1,4-butadiene, 1,4-pentadiene, 1,5-pentadiene, 1,4-hexadiene, 1,5-hexadiene, cyclopentadiene, 1,3-cyclohexadiene, 1,4-cyclohexadiene, and oxocyclohexadiene, and each diene ligand comprises one or more substituents R 1 It can be optionally substituted as, and each R 1 It is independently selected from H, O, C1 to C4 linear or branched alkyl, C1 to C4 linear or branched alkylamide, C1 to C4 linear or branched alkoxide, C1 to C4 linear or branched alkylsilyl, C1 to C4 linear or branched alkylsilylamide, and C1 to C4 linear or branched fluoroalkyl.
[0063] Particularly preferred iridium oxide precursors are (methylcyclopentadienyl)(1,3-cyclohexadiene)iridium, (ethylcyclopentadienyl)(1,3-cyclohexadiene)iridium, (ethylcyclopentadienyl)(1,5-cyclooctadiene)iridium, (1,5-cyclooctadiene)(2,2,6,6-tetramethyl-3,5-heptanethionate)iridium, (ethylcyclopentadienyl)(2,3-Me-2-1,3-butadiene)iridium, (methylcyclopentadienyl)(1,5-hexadiene)iridium, (ethylcyclopentadienyl)(1,5-hexadiene)iridium, (methylcyclopentadienyl)(1,4-butadiene)iridium, It is selected from (methylcyclopentadienyl)(1,4-pentadiene)iridium, (methylcyclopentadienyl)(1,5-pentadiene)iridium, (methylcyclopentadienyl)(1,4-hexadiene)iridium, (methylcyclopentadienyl)(1,5-hexadiene)iridium, (ethylcyclopentadienyl)(1,4-butadiene)iridium, (ethylcyclopentadienyl)(1,4-pentadiene)iridium, (ethylcyclopentadienyl)(1,5-pentadiene)iridium, (ethylcyclopentadienyl)(1,4-hexadiene)iridium and / or (ethylcyclopentadienyl)(1,5-hexadiene)iridium, or mixtures thereof.
[0064] Preferably, the iridium oxide precursor has a melting point of less than 25°C, preferably less than 0°C, and more preferably is in a liquid state at a temperature of 25°C to 45°C and at atmospheric pressure. Preferably, in the method according to the present disclosure, the iridium oxide precursor is in a liquid state at room temperature.
[0065] Preferably, in the method according to the present disclosure, the iridium oxide precursor exhibits a vapor pressure in the range of 1 to 100 torr at room temperature to 200°C.
[0066] Oxidant
[0067] Processes for treating iridium precursors typically utilize oxygen or oxidative co-reactants. However, the use of oxygen and oxidative co-reactants may be incompatible with the substrate surface. Therefore, there is a need for iridium precursors and co-reactants capable of reacting to form iridium metal and iridium-based thin films without the use of oxidative co-reactants or oxidizing agents.
[0068] Preferably, in the method according to the present disclosure, the oxidizing agent comprises a molecular oxygen source provided by the decomposition of the oxidizing agent under the conditions of step (iii).
[0069] Preferably, the oxidizing agent comprises hydrogen peroxide or a peroxide of an organic compound. More preferably, the oxidizing agent comprises hydrogen peroxide.
[0070] Reaction Conditions
[0071] Preferably, in the method according to the present disclosure, the iridium oxide precursor and / or auxiliary reactant is heated to increase the vapor pressure before step (ii) of supplying vapor to the reaction chamber.
[0072] Iridium precursor vapor or gas and / or oxidizer vapor or gas is preferably introduced into a process chamber at a flow rate of at least 10 sccm, preferably at least 50 sccm, at least 100 sccm, at least 200 sccm, in the range of 300 sccm to 400 sccm, at least 500 sccm, at least 700 sccm, at least 1000 sccm, at least 1200 sccm, at least 1500 sccm, at least 1800 sccm, or at least 2000 sccm, and comes into contact with a substrate.
[0073] For example, an iridium precursor or oxidizing agent may be introduced into a process chamber and / or exposed to a substrate at a flow rate of 10 sccm to 2000 sccm, preferably 10 sccm to 1500 sccm, more preferably 10 sccm to 1000 sccm, again preferably 10 sccm to 800 sccm, even more preferably 10 sccm to 500 sccm, again even more preferably 10 sccm to 300 sccm, 10 sccm to 100 sccm, 100 sccm to 2000 sccm, 100 sccm to 1500 sccm, 100 sccm to 1000 sccm, 100 sccm to 800 sccm, 100 sccm to 500 sccm, or 100 sccm to 300 sccm.
[0074] Carrier Gas
[0075] An iridium precursor or oxidizer may be introduced into a process chamber and / or exposed to a substrate in the form of a precursor mixture comprising an iridium precursor carried by one or more inert carrier gases or an oxidizer mixture comprising an oxidizer carried by one or more inert carrier gases.
[0076] The carrier gas may comprise one or more gases, such as nitrogen, argon, helium, or any combination thereof. Accordingly, preferably in the method according to the present disclosure, the gaseous precursor compound is transported to the reaction chamber using an inert carrier gas.
[0077] Catalyst particles
[0078] Preferably, in the method according to the present disclosure, the continuous iridium oxide film has an average layer thickness of less than 5 nm as measured by a transmission electron microscope (TEM).
[0079] The iridium oxide coated particle material obtainable by the above process comprises a continuous and uniformly distributed film of iridium oxide particles with an average layer thickness of less than 5 nm as measured by a transmission electron microscope (TEM).
[0080] Preferably, in the method according to the present disclosure, iridium oxide comprises iridium oxide (IV), iridium oxide (III) and / or a mixture thereof.
[0081] The iridium oxide coated particle material preferably contains iridium at a concentration of 30 at%, 40 at%, 50 at%, 60 at%, or 70 at% to 75 at%, 80 at%, 85 at%, 87 at%, 90 at%, 95 at%, 96 at%, 97 at%, 98 at%, or 99 at%. For example, the iridium oxide coated particle material contains iridium at a concentration of 30 at% to 99 at%, 40 at% to 99 at%, 50 at% to 99 at%, 60 at% to 99 at%, 70 at% to 99 at%, 80 at% to 99 at%, 90 at% to 99 at%, 30 at% to 90 at%, 40 at% to 90 at%, 50 at% to 90 at%, 60 at% to 90 at%, 70 at% to 90 at%, 80 at% to 90 at%, 30 at% to 80 at%, 40 at% to 80 at%, 50 at% to 80 at%, 60 at% to 80 at%, 70 at% to 80 at%, or 75 at% to 80 at%. Includes.
[0082] The above iridium material (e.g., metallic iridium or iridium oxide) is deposited or otherwise formed to a thickness of 2 Å, 5 Å, 8 Å, 10 Å, 15 Å, 20 Å, 25 Å, 30 Å, 40 Å, or 50 Å to 60 Å, 70 Å, 80 Å, 90 Å, 100 Å, 120 Å, 150 Å, 200 Å, 250 Å, 300 Å, 400 Å, 500 Å or more. For example, the iridium material is 2 Å to 500 Å, 5 Å to 400 Å, 5 Å to 300 Å, 5 Å to 200 Å, 5 Å to 150 Å, 5 Å to 100 Å, 5 Å to 80 Å, 5 Å to 50 Å, 5 Å to 25 Å, 10 Å to 400 Å, 10 Å to 300 Å, 10 Å to 200 Å, 10 Å to 150 Å, 10 Å to 100 Å, 10 Å to 80 Å, 10 Å to 50 Å, 10 Å to 25 Å, 20 Å to 400 Å, 20 Å to 300 Å, 20 Å It is deposited or otherwise formed with a thickness of 200 Å, 20 Å to 150 Å, 20 Å to 100 Å, 20 Å to 80 Å, 20 Å to 50 Å, or 20 Å to 25 Å.
[0083] Preferably, in the method according to the present disclosure, steps (ii) and (iv) are performed in a temperature range of 125°C to 375°C, and more preferably in a temperature range of 150°C to 300°C.
[0084] During the ALD process, the process chamber and / or substrate are preferably heated and / or maintained at a temperature of 0°C, 5°C, 10°C, 15°C, 20°C, 25°C, 30°C, 35°C, 40°C, 45°C, or 50°C to 60°C, 70°C, 80°C, 100°C, 120°C, 150°C, 180°C, 200°C, 250°C, 300°C, 350°C, 400°C, or 500°C. In one or more embodiments, during the ALD process, the process chamber and / or substrate are preferably heated to and / or maintained at a temperature of 0°C to 500°C, 0°C to 400°C, 0°C to 350°C, 0°C to 300°C, 0°C to 250°C, 0°C to 200°C, 0°C to 150°C, 0°C to 100°C, 0°C to 80°C, 0°C to 70°C, or 0°C to 50°C. In some embodiments, during the deposition process, the process chamber and / or substrate are preferably heated to and / or maintained at a temperature of 20°C to 500°C, 20°C to 400°C, 20°C to 350°C, 20°C to 300°C, 20°C to 250°C, 20°C to 200°C, 20°C to 150°C, 20°C to 100°C, 20°C to 80°C, 20°C to 70°C, or 20°C to 50°C.
[0085] In another embodiment, during the deposition process, the process chamber and / or substrate are preferably heated to and / or maintained at a temperature of 40°C to 400°C, 40°C to 375°C, 40°C to 350°C, 40°C to 300°C, 40°C to 250°C, 40°C to 200°C, 40°C to 150°C, 40°C to 100°C, 40°C to 80°C, 40°C to 70°C, or 40°C to 50°C.
[0086] The present invention also relates to an iridium oxide coated particle material comprising a continuous iridium oxide film, wherein the film is a conformal film comprising 3 to 5 weight percent carbon based on the iridium oxide film measured according to ASTM E1019.
[0087] The present invention also relates to an iridium oxide coated non-metallic particle material, wherein the iridium is present in a range of 5 to 50 weight percent based on the total catalyst weight measured according to ICP-OES.
[0088] The iridium oxide of the present invention is mainly composed of iridium oxide (IV) (IrO2), but various amounts of iridium oxide (III) (Ir2O3) may also be present.
[0089] In this specification, the term "particle catalyst" refers to a catalyst in which iridium oxide particles are finely deposited on a particulate substrate material or dispersed around it.
[0090] Reactors
[0091] Other suitable reactors that can be used for thin film deposition according to the process of the present invention include commercially available ALD reactors, and various types of reactors capable of thin film growth by ALD can be used, including CVD reactors equipped with appropriate equipment and means for supplying precursors in a pulsed manner.
[0092] Preferably, the method according to the present disclosure may be carried out in a batch-type fluidized bed reactor, a rotary drum reactor, or a continuous-type reactor.
[0093] Preferably, the reactor lineup is designed to remain separated from each other until the reactants reach the reaction chamber, thereby minimizing the use of shared piping for precursors. However, other configurations are also possible.
[0094] Etching
[0095] The method according to the present disclosure preferably further comprises the step of contacting the particle material with water at an elevated temperature before metal deposition to remove residual compounds and form an etched particle material. The method according to the present disclosure also relates to an etch-activated iridium oxide coated particle catalyst material having a continuous iridium oxide film that is an equiangular film containing less than 0 to 3 weight percent carbon based on the iridium oxide film as measured according to ASTM E1019.
[0096] Calcination
[0097] The method according to the present disclosure further comprises, as step (vii), a step of heat-treating an iridium oxide-coated particulate substrate in the presence of oxygen at a temperature range of 150°C to 550°C to obtain an activated iridium oxide-coated particulate catalyst material. Instead of an oxidizing atmosphere using oxygen, a reducing atmosphere such as the presence of hydrogen may be used. This heat treatment is sometimes referred to as "calcination" or "annealing."
[0098] PEM and CCM Application
[0099] The present disclosure also relates to a method for manufacturing a proton exchange membrane (PEM) electrolytic cell, comprising the steps of: mixing an activated iridium oxide coated particle catalyst material according to the present disclosure with a polymer material, preferably an ionomer, to form a catalyst-polymer dispersion; applying the catalyst-polymer dispersion onto a PTFE membrane to form a catalyst layer; and transferring the catalyst layer onto a proton exchange membrane to obtain a catalyst coating film (CCM). Furthermore, the present invention relates to a membrane electrode assembly (MEA) suitable for use in a PEM electrolytic cell stack, comprising the catalyst coating film (CCM) prepared as described above. Accordingly, the present invention also relates to the use of the activated iridium oxide coated particle catalyst material according to the present disclosure in a proton exchange membrane electrolytic cell.
[0100] For the fabrication of electrodes, catalyst coating films (CCMs), and membrane electrode assemblies (MEAs), the iridium oxide particle catalyst according to the present disclosure is preferably prepared into a polymer matrix, such as an ink or paste, by adding a suitable solvent and optionally an ionomer material. The catalyst material may be deposited on a gas diffusion layer (GDL), a current collector, an ionomer film, a blank PTFE sheet, release paper, or a separator, etc., by spraying, printing, doctor-blading, or other deposition processes. Generally, a drying process is subsequently performed to remove the solvent from the catalyst ink. In catalyst coating films (CCMs) and membrane electrode assemblies (MEAs) for PEM water electrolyzers, the catalyst material according to the present disclosure is applied to the anode side of the MEA. A typical loading amount of iridium metal is 0.2 to 2.5 mg / cm³. 2 It is a range.
[0101] Catalytic coating films (CCMs) are advantageously used in electrolysis. This applies not only to hydrogen production but also, when the principle is applied in reverse, to the fundamental principle of energy generation by fuel cells.
[0102] In these fuel cells, electrochemical reactions occur at the electrodes, and chemical energy stored in the fuel and oxidant is converted into electrical energy and heat. Electrocatalysts are used to promote the electrochemical oxidation of the fuel at the anode and the electrochemical reduction of oxygen at the cathode. Particularly in regenerative fuel cells, the electrodes must be dual-functional, and both the anode and cathode must be capable of performing two electrochemical reactions at different times. When operating as a fuel cell, the oxygen reduction reaction occurs at the cathode and the hydrogen oxidation reaction at the anode; when operating as an electrolyzer, the hydrogen evolution reaction occurs at the cathode and the oxygen evolution reaction at the anode. Therefore, it may be desirable to include both conventional hydrogen oxidation catalysts and oxygen evolution catalysts in the anode of such fuel cells, and with this configuration, the anode can effectively perform both hydrogen oxidation and oxygen evolution reactions.
[0103] Various electrocatalysts for oxygen evolution reactions are known in the art. For example, WO2005 / 049199 discloses a catalyst for water electrolysis. Additionally, WO2011 / 021034 discloses a catalyst layer comprising an electrocatalyst and an oxygen evolution reaction catalyst, wherein the oxygen evolution reaction catalyst comprises iridium or iridium oxide and one or more metals M or oxides thereof, wherein M is selected from the group consisting of transition metals excluding ruthenium and Sn. EP2475034 discloses a catalyst layer comprising a combination of an iridium oxide component and at least one other inorganic oxide component. WO2016 / 038349 discloses a method for preparing a catalyst comprising iridium oxide and a metal oxide by flame spray pyrolysis. However, there is a need for improved oxygen evolution reaction catalysts, and in particular, it is desirable to provide a catalyst capable of improving the stability of a membrane electrode assembly during repeated polarity reversal events.
[0104] Hereinafter, various embodiments of the present invention will be described with reference to the drawings illustrating preferred exemplary embodiments of the present invention.
[0105] FIG. 1 shows the shape of an iridium oxide (IrOx) catalyst according to a preferred embodiment of the present disclosure using a transmission electron microscope (TEM) image.
[0106] The applicant confirmed that iridium oxide is uniformly distributed across the entire surface of the substrate by initial deposition, as illustrated in FIG. 1. Here, iridium oxide forms a film of discontinuous but conformal iridium oxide crystals or metal clusters.
[0107] The applicant confirmed that after calcination, this shape changes and larger iridium oxide clusters may be formed, but these are also uniformly distributed across the entire particle surface.
[0108] FIG. 2 shows the results of evaluating durability relative to activity by comparing the mass activity and electrochemical active area (ECA) performance of a catalyst composition according to a preferred embodiment of the present disclosure in a rotating disk electrode (RDE) electrochemical test with that of Iridium Black, a commercial iridium oxide catalyst. From the perspective of performance improvement, it appears desirable to use a conductive support with no or few such pores, unlike catalysts of the prior art. Accordingly, particulate substrates such as boron carbide can exhibit higher performance.
[0109] FIG. 3 shows the iridium-4f region of the XPS spectrum (Al Kα radiation) of samples having different iridium oxidation states of various catalyst compositions according to a preferred embodiment of the present disclosure, using X-ray photoelectron spectroscopy (XPS), showing states from amorphous Ir(III) to more oxidized Ir(IV).
[0110] FIG. 4 shows the 0.5-fold current density of the catalyst composition according to a preferred embodiment of the present disclosure compared with a commercially available comparative catalyst in a membrane electrode assembly (MEA) test. From top to bottom, 2.4 g / cm² 2 Comparative example using Pt-PTL, Iridium Black, 2.4 g / cm³ 2 The performance of Iridium Black, a comparative example using Ti-PTL, Example 1: IrOx on B4C using Pt-PTL 5% Nafion, Example 2: IrOx on B4C using Pt-PTL 5% Nafion, and Example 3: IrOx on B4C using Pt-PTL 10% Nafion is shown, and these examples have a value of 0.077 to 0.145 g / cm³ 2 It clearly shows that similar activity is exhibited even at iridium concentrations 15 to 30 times lower than the catalyst loading amount.
[0111] Figure 5 is a table showing the change in electrical conductivity when an etching treatment is applied to a support and a calcined catalyst. In each case, the etching treatment improves the electrical conductivity of the powder.
[0112] Figure 6 is a graph showing the relationship between cell voltage and current density at the initial performance (BoL) of the catalyst particles. Comparative examples of catalysts with different iridium loading amounts and Iridium Black are shown. This clearly demonstrates that the catalyst particles according to the present disclosure exhibit a much higher iridium utilization rate as a result of testing in a PEM electrolyzer.
[0113] Figure 7 is a graph showing the relationship between voltage and current density at the initial performance (BoL), the start time of the accelerated degradation test (BoT), and the end time of the accelerated degradation test (EoT). The catalyst particles according to the embodiments of this specification exhibit somewhat lower performance at the initial performance (BoL), but as the iridium loading increases, they gradually approach the performance of the Iridium Black reference catalyst at each iteration of the CCM. Example 2 has a catalyst particle loading per area of 0.15 mg / cm² 2 In contrast, the Iridium Black comparative example has a loading amount per area of 2.4 mg / cm² 2 The catalyst of the example exhibits performance nearly similar to the Iridium Black comparative example, despite the iridium usage being reduced by 16 times.
[0114] Therefore, it is evident that the catalyst according to the present disclosure can exhibit an equivalent or higher current density even at a much lower iridium concentration than the Iridium Black catalyst representative of the prior art when the loading amount of iridium oxide is increased.
[0115] Examples
[0116] The following non-limiting examples illustrate processes and materials according to the present disclosure. Here, four types of catalyst compositions were prepared and compared with two types of reference catalysts.
[0117] Electrochemical Measurement
[0118] The electrochemical properties of the catalyst material are current density (mA / cm²) at 1.5 V versus RHE (RHE: reversible hydrogen electrode). 2It was evaluated by ) and mass activity (A / mg). In this test, the catalyst sample was dispersed in ultrapure water and immobilized on a gold carbon electrode. Cyclic voltammograms were measured using a sulfuric acid (c=0.05 mol / L) solution at room temperature (20°C). A gold (Au) electrode was used as the counter electrode, a reversible hydrogen electrode (GasKatel) was used as the reference electrode, and the scan speed was 20 mV / s. After performing 50 conditioning cycles, a third voltammogram scan was measured to establish quasi-stationary conditions. Electrochemical mass activity was calculated based on the current value at a constant voltage of 1.5 V versus RHE.
[0119] Membrane electrode assembly (MEA) tests
[0120] For the MEA test, a catalyst coating film (CCM) was fabricated and evaluated using a custom-made MEA test apparatus. To fabricate the CCM, an ink containing catalyst powder, a solvent, Nafion, and other additives was prepared. The catalyst ink was screen-printed onto a decal sheet. Subsequently, the catalyst layer was transferred from the decal sheet to a Nafion 115 film by hot pressing to produce the CCM. Afterward, the CCM was assembled into an MEA containing a titanium porous transport layer (PTL), and the MEA was mounted within a cell housing. After mounting the MEA, water at 40°C was supplied to the cell housing to wet the CCM for 30 minutes. After 30 minutes, the cell housing was heated to 80°C at a heating rate of 0.5°C / minute while a cell voltage of 2 V was applied. The cell voltage was applied for 24 hours, after which the following steps were performed.
[0121] During the initial performance (BoL) measurement, the polarization curve (IV-curve) was recorded. The polarization curve was measured as a stepwise V curve, gradually lowering the voltage from 2 V to 1.45 V and then raising it back to 2 V, with each step maintained for 3 minutes. At each measurement point, the current recorded during the last 30 seconds was averaged, and the corresponding polarization curve was constructed using the curve obtained during the voltage increase process. After the BoL performance measurement, the cell voltage was set to 2 V and maintained for 40 hours to measure the current over time as an indicator to evaluate the degree of degradation. After 40 hours, the final test (EoT) performance measurement was performed using the same method as the BoL performance measurement.
[0122] Measurement of Electrical Conductivity
[0123] The electrical conductivity of the sample was measured using a self-made measuring device. The measuring device consists of a structure in which a force sensor (Burster Sensormaster 9163), a displacement sensor (Aiggend, 0–12.7 mm), and a resistance sensor (HP 4338B Milliohmmeter) are connected to two brass pistons inserted into a plastic container. After filling the container with the powder sample (sample radius: 3.0 mm, sample weight: 0.05–0.1 g), the electrical conductivity was measured while increasing the pressure from 0 MPa to 7 MPa during the measurement.
[0124] Atomic Layer Chemical Vapor Deposition
[0125] An iridium precursor, which is in a liquid state at room temperature and suitable for depositing iridium films in a temperature range of 150°C to 375°C, was stored in a flask equipped with a bubbler and maintained at 60°C using nitrogen as an inert gas. After the substrate was introduced into the fluidized bed, the iridium precursor vapor was drawn from the flask and supplied to the fluidized bed reactor in the form of a diluted vapor by bubbling an inert gas into the heated precursor liquid. After the reaction was mostly finished, the oxidizing agent co-reactant gas was introduced into the fluidized bed within the reactor. In ALD technology, metallic iridium can be deposited not only when the co-reactant is molecular oxygen or atomic oxygen, but also when other oxidizing agents are used.
[0126] Examples 1 to 4 were prepared by sequentially contacting the substrate with alternating pulses of an iridium precursor gas and an oxidizing agent gas, thereby depositing an increasing amount of iridium. After deposition, the catalyst particles were calcined in an oxygen atmosphere.
[0127] MEA tests
[0128] Table 1 shows the difference in current density according to the metal loading amount for each embodiment and two comparative examples according to the present disclosure.
[0129]
[0130] The Iridium Black samples used in the comparative examples utilized a standard porous transport layer (PTL) in Comparative Example 1 and a platinum-coated PTL in Comparative Example 2. Examples 1 to 3 relate to iridium oxide films formed on boron carbide substrates having an average particle size of 45 to 55 nm, which were prepared by chemical vapor deposition using an iridium heterolaptic metallocene complex that is in a liquid state at room temperature. Example 1 contains a standard titanium PTL and contains 33 wt% IrOx. Examples 2 and 3 contain a platinum-coated PTL and contain 33 wt% and 26 wt% IrOx, respectively.
[0131] Test Example 2: Evaluation of catalyst performance, oxygen evolution reaction (OER) activity, and stability in rotating disk electrode (RDE) electrochemical tests (Performance of catalyst in rotating disk electrode (RDE) electrochemical tests, Oxygen Evolution Reaction (OER) Activity and Stability Benchmarks)
[0132]
[0133] Examples 1 and 2 exhibit equivalent durability and much higher oxygen evolution reaction (OER) activity compared to the commercial standard catalysts of Comparative Examples 1 and 2. This once again clearly demonstrates that the catalyst material according to the present invention possesses unique characteristics, represented by high durability and excellent OER activity, when compared to current industry standards.
[0134] The foregoing is intended to illustrate the invention and should not be construed as limiting the invention. Although several exemplary embodiments of the invention have been described, those skilled in the art will readily understand that various modifications to these exemplary embodiments are possible without substantially departing from the novel technical spirit and advantages of the invention. Accordingly, all such modifications are intended to be included within the scope of the invention as defined by the claims.
[0135] Accordingly, the foregoing description is intended to illustrate the invention and should not be interpreted as being limited to the specific embodiments disclosed, and modifications to the disclosed embodiments as well as other embodiments are intended to be included within the scope of the appended claims. The scope of the invention is defined by the following claims, and equivalents thereof are also included within the scope of the invention.
Claims
Claim 1 A method for forming an iridium oxide film by chemical vapor deposition on a particulate substrate having an electrical conductivity exceeding 0.01 S / cm based on powder measurement standards, comprising: (i) providing the particulate substrate in a reaction chamber; (ii) contacting the particulate substrate with a vaporized iridium oxide precursor gas to form a film of an iridium precursor material uniformly distributed on the substrate; (iii) contacting the material including the uniformly distributed layer with a vaporized oxidizing agent to cause the oxidizing agent to react with the iridium precursor film uniformly distributed on the substrate; and (iv) optionally repeating steps (ii) and (iii), and obtaining a particulate material having a surface film of a desired thickness comprising uniformly distributed individual iridium oxide clusters having an average diameter of 0.3 to 5 nm as measured by a transmission electron microscope (TEM). Claim 2 A method according to claim 1, comprising the step of sequentially exposing the particulate substrate to a gaseous iridium precursor and a gaseous oxidizing agent to deposit an iridium material on the substrate. Claim 3 A method according to claim 1 or 2, comprising the step of removing excess iridium oxide precursor gas, excess reaction gas and / or reaction by-products from the reaction chamber. Claim 4 A method according to claim 1 or 2, wherein excess iridium oxide precursor gas, excess reaction gas and / or reaction by-products are not removed from the reaction chamber. Claim 5 A method according to any one of claims 1 to 4, wherein steps (ii) and (iii) are supplied such that the iridium oxide precursor gas causes a self-terminating reaction with the surface of the particulate substrate, and the oxidizing agent causes a self-terminating reaction with the surface of the particle comprising a continuous iridium oxide precursor material layer. Claim 6 A method according to any one of claims 1 to 5, wherein steps (i) to (iv) are performed in a pressure range of 80 to 1010 kPa, preferably at atmospheric pressure or a pressure close to atmospheric pressure. Claim 7 A method according to any one of claims 1 to 6, wherein the iridium oxide precursor comprises an organometallic complex of iridium. Claim 8 The method according to claim 7, wherein the iridium oxide precursor comprises an iridium (C1 to C4-alkylcyclopentadienyl) complex, preferably a methylcyclopentadienyl complex or an ethylcyclopentadienyl complex. Claim 9 A method according to claim 7 or 8, wherein the iridium oxide precursor is a heterolaptic metallocene complex. Claim 10 In claim 8 or 9, the (C1 to C4-alkylcyclopentadienyl) complex further comprises a diene ligand selected from linear or cyclic alkylenes, preferably selected from 1,4-butadiene, 1,4-pentadiene, 1,5-pentadiene, 1,4-hexadiene, 1,5-hexadiene, cyclopentadiene, 1,3-cyclohexadiene, 1,4-cyclohexadiene, and oxocyclohexadiene, wherein each diene ligand comprises one or more substituents R 1 It can be optionally substituted as, and each R 1 A method independently selected from H, O, C1 to C4 linear or branched alkyl, C1 to C4 linear or branched alkylamide, C1 to C4 linear or branched alkoxide, C1 to C4 linear or branched alkylsilyl, C1 to C4 linear or branched alkylsilylamide, and C1 to C4 linear or branched fluoroalkyl. Claim 11 In claim 10, the iridium oxide precursor is (methylcyclopentadienyl)(1,3-cyclohexadiene)iridium; (ethylcyclopentadienyl)(1,3-cyclohexadiene)iridium; (ethylcyclopentadienyl)(1,5-cyclooctadiene)iridium, (1,5-cyclooctadiene)(2,2,6,6-tetramethyl-3,5-heptanethionate)iridium; (ethylcyclopentadienyl)(2,3-Me-2-1,3-butadiene)iridium; (methylcyclopentadienyl)(1,5-hexadiene)iridium; (ethylcyclopentadienyl)(1,5-hexadiene)iridium, (methylcyclopentadienyl)(1,4-butadiene)iridium, (methylcyclopentadienyl)(1,4-pentadiene)iridium, (methylcyclopentadienyl)(1,5-pentadiene)iridium, (methylcyclopentadienyl)(1,4-hexadiene)iridium, (methylcyclopentadienyl)(1,5-hexadiene)iridium; A method selected from (ethylcyclopentadienyl)(1,4-butadiene)iridium, (ethylcyclopentadienyl)(1,4-pentadiene)iridium, (ethylcyclopentadienyl)(1,5-pentadiene)iridium, (ethylcyclopentadienyl)(1,4-hexadiene)iridium and (ethylcyclopentadienyl)(1,5-hexadiene)iridium. Claim 12 A method according to any one of claims 1 to 11, wherein the iridium oxide precursor has a melting point of less than 25°C, preferably less than 0°C, and more preferably is in a liquid state at a temperature of 25°C to 45°C and at atmospheric pressure. Claim 13 A method according to any one of claims 1 to 12, wherein the oxidizing agent comprises a molecular oxygen source provided by the decomposition of the oxidizing agent under the conditions of step (iii). Claim 14 A method according to any one of claims 1 to 13, wherein the oxidizing agent comprises a hydrogen peroxide or a peroxide of an organic compound, preferably the oxidizing agent comprises hydrogen peroxide. Claim 15 A method according to any one of claims 1 to 14, wherein steps (ii) and (iii) are performed in a temperature range of 125°C to 375°C, preferably in a temperature range of 150°C to 300°C. Claim 16 A method according to any one of claims 1 to 15, wherein the iridium oxide precursor and / or oxidizing agent auxiliary reactant is heated to increase the vapor pressure before step (ii) of supplying vapor to the reaction chamber. Claim 17 A method according to any one of claims 1 to 16, wherein the precursor compound and / or oxidizing agent auxiliary reactant in a vapor or gaseous state is transported to a reaction chamber using an inert carrier gas. Claim 18 A method according to any one of claims 1 to 17, performed in a batch fluidized bed reactor, a rotary drum reactor, or a continuous reactor. Claim 19 A method according to any one of claims 1 to 18, wherein the support material is essentially inert under oxidizing and acidic conditions, and preferably the support material is inert during deposition of an iridium oxide layer, during firing, during etching, and while used in a PEM electrolytic cell. Claim 20 A method according to any one of claims 1 to 19, wherein the particulate support material comprises a metal oxide, a carbide, a boride, a nitride, and a non-metal oxide and / or carbide. Claim 21 In claim 20, the particulate substrate is selected from inorganic metal oxides, preferably selected from the group consisting of titania (TiO2), silica (SiO2), alumina (Al2O3), zirconia (ZrO2), tin dioxide (SnO2), fluorine-doped tin dioxide (SnO2 / F), ceria (CeO2), ceria-doped zirconia (CeO2 / ZrO2), niobium pentoxide (Nb2O5), tantalum pentoxide (Ta2O5), and mixtures and combinations thereof, or selected from boron carbide materials or boron carbide composites with other compounds such as silicon carbide. Claim 22 A method according to any one of claims 1 to 21, wherein the particle size of the supporting material is a weight-average particle size in the range of 10 nm to 100 nm, preferably in the range of 40 nm to 60 nm. Claim 23 A method according to any one of claims 1 to 22, wherein the continuous film of uniformly distributed iridium oxide has an average layer thickness of less than 5 nm as measured by a transmission electron microscope (TEM). Claim 24 A method according to claim 22 or 23, wherein the iridium oxide comprises iridium oxide (IV), iridium oxide (III), metallic iridium (Ir(0)) and / or a mixture thereof. Claim 25 A method according to any one of claims 22 to 24, wherein the inorganic oxide is added in a range of 30% to 60% by weight based on the total weight of the catalyst. Claim 26 A method according to any one of claims 1 to 25, further comprising the step of contacting the particle material with water at a heated temperature before metal deposition to remove residual compounds and form an etched particle material. Claim 27 A method according to any one of claims 1 to 26, further comprising the step (vii) of obtaining an activated iridium oxide coated particle catalyst material by calcining the iridium oxide coated particle substrate in the presence of oxygen at a temperature range of 150°C to 550°C. Claim 28 A method according to any one of claims 1 to 27, further comprising the step of contacting the calcined activated iridium oxide coated particle catalyst with water at an elevated temperature to remove residual compounds and form an etched activated iridium oxide coated particle catalyst material. Claim 29 An iridium oxide coated particle material obtainable by the method of any one of claims 1 to 28, comprising a continuous film of uniformly distributed iridium oxide with an average layer thickness of less than 5 nm as measured by a transmission electron microscope (TEM). Claim 30 In claim 29, the iridium oxide coated particle material is an iridium oxide film that is an conformal film further comprising 3 to 5 weight percent of carbon-containing residue based on the iridium oxide film when measured according to ASTM E1019. Claim 31 An iridium oxide coated non-metallic particle material according to claim 29 or 30, wherein the iridium is present in a range of 5 to 50 weight% based on the total catalyst weight measured according to ICP-OES. Claim 32 An etched activated iridium oxide coated particle catalyst material obtainable by the method of claim 27, wherein the continuous iridium oxide film is an equiangular film containing less than 0 to 3 weight percent of carbon based on the iridium oxide film when measured according to ASTM E1019. Claim 33 A method for manufacturing a proton exchange membrane (PEM) electrolytic cell comprising: a. mixing an activated iridium oxide coated particle catalyst material according to any one of claims 29 to 32 with a polymer material, preferably an ionomer, to form a catalyst-polymer dispersion; b. applying the catalyst-polymer dispersion onto a PTFE membrane to form a catalyst layer; and c. transferring the catalyst layer to a proton exchange membrane to obtain a catalyst coating film (CCM). Claim 34 A membrane electrode assembly (MEA) suitable for use in a PEM electrolytic cell stack, comprising a catalyst coating film (CCM) prepared according to the method of claim 33. Claim 35 Use of an activated iridium oxide coated particle catalyst material according to any one of claims 29 to 32 in a proton exchange membrane electrolytic cell.
